2023
DOI: 10.1021/acsnano.2c11305
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Target of Intratumoral Microbiome and Tumor by Metronidazole–Fluorouridine Nanoparticles

Abstract: Clinical and experimental evidence confirmed bacterial infiltration in a variety of tumors, which is related to the progression and therapeutic effects of the tumors. Although the administration of antibiotics inhibits the growth of bacteria inside the tumor, systemic distribution of antibiotics induces an imbalance of other microbiomes in the body, which in turn leads to the development of new diseases. To address this clinical challenge, we nanonized an antibiotic in this study. Metronidazole, an antibiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 48 publications
(68 reference statements)
0
8
0
Order By: Relevance
“…5A). 91 Both in vitro and in vivo results revealed that the as-designed nanoparticles presented synergistic effects targeting both the intra-tumoral microbiome and tumour cells, suggesting a potential strategy to kill pro-tumour bacteria efficiently and maintain a balanced microbiota composition in the patient. Roger Geiger and Federica Sallusto found that engineered probiotic E. coli Nissle 1917 strain colonizing tumour could increase the level of tumour-infiltrating T cells and synergize with PD-L1 therapeutic effects via increasing the intra-tumoral l -arginine concentration.…”
Section: Drug Delivery Systems For Intra-tumoral Bacterial Therapymentioning
confidence: 99%
“…5A). 91 Both in vitro and in vivo results revealed that the as-designed nanoparticles presented synergistic effects targeting both the intra-tumoral microbiome and tumour cells, suggesting a potential strategy to kill pro-tumour bacteria efficiently and maintain a balanced microbiota composition in the patient. Roger Geiger and Federica Sallusto found that engineered probiotic E. coli Nissle 1917 strain colonizing tumour could increase the level of tumour-infiltrating T cells and synergize with PD-L1 therapeutic effects via increasing the intra-tumoral l -arginine concentration.…”
Section: Drug Delivery Systems For Intra-tumoral Bacterial Therapymentioning
confidence: 99%
“…Gao et al designed a nanoformulated metronidazole, a broadspectrum antibiotic targeting anaerobic bacteria, and conjugated it with fluorouracil to produce an amphiphilic small molecule, metronidazole-fluorouracil, followed by self-assembling in aqueous solutions to form GSH-responsive metronidazole-fluorouracil nanoparticles (MTI-FDU). 66 MTI-FDU reshapes the TIME by eliminating bacteria and bacterial byproducts, demonstrating clinical benefits in treating tumors infiltrated with bacteria as this nanomedicine can effectively kill tumor-promoting bacteria while maintaining the patient's microbiome balance. Additionally, Chen et al recently reported a Fusobacterium-targeted liposome designed for colorectal cancer treatment, which is able to targetedly deliver antibiotics to immunosuppressive bacteria.…”
Section: Intratumoral Bacterial Clearancementioning
confidence: 99%
“…However, systemic antibiotic administration can disrupt the balance of other microbial communities in the body, potentially resulting in the emergence of new diseases. Gao et al designed a nanoformulated metronidazole, a broad-spectrum antibiotic targeting anaerobic bacteria, and conjugated it with fluorouracil to produce an amphiphilic small molecule, metronidazole-fluorouracil, followed by self-assembling in aqueous solutions to form GSH-responsive metronidazole-fluorouracil nanoparticles (MTI-FDU) . MTI-FDU reshapes the TIME by eliminating bacteria and bacterial byproducts, demonstrating clinical benefits in treating tumors infiltrated with bacteria as this nanomedicine can effectively kill tumor-promoting bacteria while maintaining the patient’s microbiome balance.…”
Section: Intratumoral Bacterial Clearancementioning
confidence: 99%
“…To address these clinical challenges, Gao et al. 231 nanonized the antibiotic metronidazole by linking it with fluorouridine via disulfide bond linker to prepare an amphiphilic small molecule, which could self-assembled into nanoparticles and disassemble to release these two naïve drugs under high levels of glutathione in TME ( Fig. 2 A–C) 231 .…”
Section: Multidisciplinary Approach-based Interventions Of Tumor Micr...mentioning
confidence: 99%
“… 231 nanonized the antibiotic metronidazole by linking it with fluorouridine via disulfide bond linker to prepare an amphiphilic small molecule, which could self-assembled into nanoparticles and disassemble to release these two naïve drugs under high levels of glutathione in TME ( Fig. 2 A–C) 231 . The as-prepared platform could achieve synergistic antitumor effect by dual-target of both intratumoral microbiome and tumor cells, which could not only attack bacteria inside the tumor, but also re-shape TIME through clearance of bacteria and bacterial products, especially inactivating F. nucleatum related signaling pathways.…”
Section: Multidisciplinary Approach-based Interventions Of Tumor Micr...mentioning
confidence: 99%